Specific Photothermal Ablation Therapy of Endometriosis by Targeting Delivery of Gold Nanospheres. Issue 15 (1st February 2017) - Guo, Xiaomeng; Li, Wei; Zhou, Jialin; Hou, Wanqing; Wen, Xue; Zhang, Hanbo; Kong, Fenfen; Luo, Lihua; Li, Qingpo; Du, Yongzhong; You, Jian
Abstract : Endometriosis is difficult to treat since the side effects of the current therapeutic method and the high recurrence rate; thus, newer and safer therapeutic approaches are urgently needed. This work investigates the enhanced permeability and retention effect of CdTe quantum dots (QDs) and hollow gold nanospheres (HAuNS) in endometriosis to increase the delivery of HAuNS into lesion cells. The surface of HAuNS is successfully conjugated with a TNYL peptide that has specific affinity for the EphB4 receptor, which is a member of the Eph family of receptor tyrosine kinases. It is found that the EphB4 receptor is overexpressed in endometriosis lesions. The data indicate that both QDs and HAuNS can efficiently accumulate in endometriotic lesions through permeable vessels and the TNYL‐conjugated HAuNS (TNYL‐HAuNS) accumulate more via the interaction with EphB4. The specific photothermal ablation therapy based on TNYL‐HAuNS significantly inhibits the growth of the endometriotic volume and induces the atrophy and degeneration of ectopic endometrium with no detectable toxicity to the normal organs. The level of TNF‐α and estradiol also significantly decreases in the endometriotic lesions, indicating that the treatment enables a recovery from hormonal imbalance and inflammatory injury. This work can be a valuable reference for future endometriosis therapy. Abstract : The specific photothermal therapy based on EphB4 receptor targeted hollow gold nanospheres (HAuNS) significantly inhibits the growth of the endometriotic volume and induces the atrophy of the endometriosis with no detectable toxicity to the normal organs. The level of TNF‐α and estradiol also decreased in the lesions, indicating that the treatment enabled a recovery from hormonal imbalance and inflammatory injury.